2022
DOI: 10.3390/gels8020084
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Adrenal Pheochromocytoma (PC-12) Cell Proliferation and Outgrowth Using Schwann Cell-Laden Gelatin Methacrylate Substrate

Abstract: Peripheral nerve injuries cause different degrees of nerve palsy and function loss. Due to the limitations of autografts, nerve tissue engineering (TE) scaffolds incorporated with various neurotrophic factors and cells have been investigated to promote nerve regeneration. However, the molecular mechanism is still poorly understood. In this study, we co-cultured Schwann cells (SCs) and rat adrenal pheochromocytoma (PC-12) cells on 50% degrees of methacryloyl substitution gelatin methacrylate (GelMA) scaffold. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…A study found that the Achyranthes bidentata polypeptides with 0.5 µg/mL for 24h could signi cantly promote the proliferation of primary SCs cultured in vitro at different times (58). The coculture, SCs, and Adrenal Pheochromocytoma (PC-12) cells showed a numerous cell proliferation rate and axonal expansion (59). Heregulin 10nM for 24h has an effective mitogen for human SCs.…”
Section: Discussionmentioning
confidence: 99%
“…A study found that the Achyranthes bidentata polypeptides with 0.5 µg/mL for 24h could signi cantly promote the proliferation of primary SCs cultured in vitro at different times (58). The coculture, SCs, and Adrenal Pheochromocytoma (PC-12) cells showed a numerous cell proliferation rate and axonal expansion (59). Heregulin 10nM for 24h has an effective mitogen for human SCs.…”
Section: Discussionmentioning
confidence: 99%
“…The co-culture of SCs and adrenal pheochromocytoma (PC-12) cells showed a high cell proliferation rate and axonal expansion (62). Also, Heregulin (10 nM) for 24 h showed a successful mitogen for human SCs (63).…”
Section: Discussionmentioning
confidence: 99%
“…A survey showed that the Achyranthes bidentata polypeptides at 0.5 μg/mL for 24 h could significantly promote the proliferation of primary SCs cultured in vitro at different times ( 61 ). The co-culture of SCs and adrenal pheochromocytoma (PC-12) cells showed a high cell proliferation rate and axonal expansion ( 62 ). Also, Heregulin (10 nM) for 24 h showed a successful mitogen for human SCs ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…41 The co-culture model was constructed with fibroblasts encapsulated in GelMA, whereas melanoma cells were cultured on the GelMA surface, which realistically mimics the melanoma TME structure. 42 This co-culture model could provide a better understanding of the mechanism underlying melanoma metastasis and be further used for high-throughput drug screening or personalized therapy using cells derived from patients in the future. For material characterization, the pore structure, pore size, mechanical properties, and biodegradability of GelMA used in this study were analyzed to determine the applicability as the cell culture substrate for fibroblast encapsulation and melanoma cell seeding.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, gelatin retains the major functional peptides of collagen and had good biological properties like collagen, including good biocompatibility, biodegradability, nonimmunogenicity, and water-solubility, which makes it an ideal 3D cell culture substrate to mimic the melanoma ECM . The co-culture model was constructed with fibroblasts encapsulated in GelMA, whereas melanoma cells were cultured on the GelMA surface, which realistically mimics the melanoma TME structure . This co-culture model could provide a better understanding of the mechanism underlying melanoma metastasis and be further used for high-throughput drug screening or personalized therapy using cells derived from patients in the future.…”
Section: Introductionmentioning
confidence: 99%